Antecedents and Consequences of The Role of Trust in Mediation of Perceived Ease of Use, Risk and E-Service Quality on Online Purchase Intention - C. Catur Widayati; Nugroho, Arissetyanto; Wiyanto, Hendra; Budiono, Herlina (Dinasti International Journal of Digital Business Management, 2023)
This research aims to find out the direct influence perceived ease of use, risk perception and E-Service Quality on buying trust and interest, and also to find out the indirect influence perceive ease of use, risk perception and E-Service. Quality of trust-mediated buying interests. The population in this study was all shopee users in the Jakarta region. In this study differs from previous research by using different variables and models in this study. The methods used in this research are quantitative analysiswith SEM analysis tools and SmartPLS 3.3 tools. The findings in this study are: (1) Perceived easy of use has a significant positive effect on the purchase intention of Shopee users in Jakarta. (2) Perceived easy of use has a significant positive effect on shopee user trust in Jakarta. (3) Risk perception has a significant negative effect on the purchase intention of Shopee users in Jakarta. (4) Risk perception has a significant negative effect on shopee user trust in Jakarta. (5) Service quality has a significant positive effect on the purchase intention of Shopee users in Jakarta. (6) Service quality has a significant positive effect on shopee user trust in Jakarta. (7) Trust has a significant positive effect on the buying interest of Shopee users in Jakarta. (8) Trust is not a mediation variable in influencing risk perception of purchase intention in Shopee Users in Jakarta.